STRATEGI BAURAN PEMASARAN (MARKETING MIX) DALAM MENARIK MINAT PELANGGAN UMAH HOSHI VILLA DI DESA SEBATU, KECAMATAN TEGALLALANG - Olifia, Ni Wayan Monik Jesika; Mahaputra, Ida I Dewa Rai (Jurnal Ilmiah Manajemen & Bisnis, 2018)
Marketing Mix Strategy to Attract Consumers’ Interest of Umah Hoshi Villa at Sebatu Village,Tegallalang. This research aims to determine the marketing mix strategy used by Umah Hoshi Villa in Sebatu Village, Tegallalang Sub district in attracting customer interest. The analytical method used is descriptive analysis and SWOT analysis consisting of IFAS / EFAS matrix, IE matrix and SWOT matrix. Based on the analysis found that the strategy applied by Umah Hoshi Villa is a Marketing Mix Strategy. In IE matrix analysis, it was found that Umah Hoshi Villa's position is in quadrant IV with IFAS total score 3.1 and 2.78 for EFAS total score in which the stability strategy is a strategy that is implemented without changing the direction of the predetermined strategy. In the SWOT matrix there are four alternative strategies that can be applied by Umah Hoshi Villa. In the SO strategy, (1) with increasingly sophisticated technology, it can be easier to promote the strengths of the company, (2) by providing regular training to employees, the company always provides the best quality service, (3) attracts consumers by conducting travel packages programs at tourist attractions. In the ST strategy, (1) can make product innovations continually and provide different facilities than competitors, (2) maintain loyal customers by maximizing services so that customers feel comfortable, (3) offering attractive rates without decreasing product quality and service. In the WO strategy, (1) issuing an attractive promo package by utilizing a website so that it can meet customer needs, (2) build a brand image. Furthermore, in the WT strategy, (1) issuing attractive promo packages, (2) utilizing website to update all information about the promos that will be issued, (3) analyzing price components, facilities, and service quality in similar hotels or villas.Keywords: Marketing Mix, SWOT Analysis, SWOT Matrix